2021
DOI: 10.1186/s12903-021-01891-8
|View full text |Cite
|
Sign up to set email alerts
|

Interradicular distance and alveolar bone thickness for miniscrew insertion: a CBCT study of Persian adults with different sagittal skeletal patterns

Abstract: Background This study aimed to assess the interradicular distance and alveolar bone thickness of Persian adults with different sagittal skeletal patterns for miniscrew insertion using cone-beam computed tomography (CBCT). Methods This cross-sectional study was conducted on maxillary and mandibular CBCT scans of 60 patients (18–35 years) in three groups (n = 20) of class I, II and III sagittal skeletal pattern. Anatomical and skeletal parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Generally, the most site at level 6 mm from CEJ and at level 8 mm from CEJ is suitable for mini-implant insertion except between central and lateral. The safer area between (6-7) gives a large buccal and middle inter-radicular distance Similar findings were reported by [22] and also by [19] and [14] , and in contrasting Poggio et al, 2006 [16] who reported that the site of (6-7) and (4-5) is safer. The minimum inter-radicular spaces were observed on the buccal aspect of both jaws between the central and lateral incisors and this finding agrees with a study by Seyed Hossein Moslemzadeh et al [14] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Generally, the most site at level 6 mm from CEJ and at level 8 mm from CEJ is suitable for mini-implant insertion except between central and lateral. The safer area between (6-7) gives a large buccal and middle inter-radicular distance Similar findings were reported by [22] and also by [19] and [14] , and in contrasting Poggio et al, 2006 [16] who reported that the site of (6-7) and (4-5) is safer. The minimum inter-radicular spaces were observed on the buccal aspect of both jaws between the central and lateral incisors and this finding agrees with a study by Seyed Hossein Moslemzadeh et al [14] .…”
Section: Discussionsupporting
confidence: 83%
“…A minimum of 1 mm clearance from the alveolar bone around the mini implant has been suggested for periodontal health. Thus, the inter-radicular distance should be more than 3 mm for mini-implant placement [22] . The current study showed buccal inter-radicular distance wider than the middle interradicular distance in most sites in the upper and lower jaw and the differences were significant at P-value<0.05 this may be attributed to root anatomy, root angulation, and tooth position.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, non-invasive cone-beam computer tomography (CBCT) technology had several advantages in evaluating bone structures around teeth and offers a nancial advantage for the patient [12] . High-resolution images of CBCT can not only measure the bone thickness at the recipient site, but also help to determine the morphological characteristics of the residual alveolar process and evaluate the loss of alveolar bone [13][14][15] and allows full 3D characterization of alveolar bone. Although some CBCT studies have been conducted to analyze bone thickness in maxillary teeth, the information regarding bone thickness combined with age and gender factors in the in uence have been under-represented.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in most patients, only the apical portion of the dental roots is present in the ANS region. Therefore, the apical inter-radicular space between these roots is larger than that between the middle part, rendering it more likely to accommodate mini-implants [35,36] without damaging the roots.…”
Section: Discussionmentioning
confidence: 99%